Harvesting and stocking in discrete-time contest competition models with open problems and conjectures - Al-Sharawi, Ziyad (2016)
In this survey, we present a class of first and second-order difference equations representing general form of discrete models arising from single-species with contest competition. Then, we consider various harvesting/stocking strategies and discuss their effect on stability, persistence and maximum sustainable yield. The main aim of this work is to give an account of recent results on the subject within a unified framework, then present some open questions and conjectures that deserve further investigation.